Cluster Analysis for the Determination of Innovative and Sustainable Oriented Regions in Europe - Pelau, Corina; Chinie, Alexandra Catalina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
In the past decades the preoccupation of decision-makers towards innovation and sustainable development has gained a major importance in the policy of most countries in Europe. On one hand, efficient innovation can differentiate a country or a region from another and make a difference in the intense increasing economic, technological and social competition. On the other hand, the orientation towards sustainable development assures a clean and unpolluted, social oriented and healthy environment as a framework for the growth of a country or a region. In many cases, innovation and sustainable development go hand in hand, as innovations contribute to the development of clean technologies, while sustainable societies assure the proper environment and background for stimulating the innovation research. The objective of this research is to determine the cluster of countries in Europe which are rather oriented to innovation or to sustainable development or both and to forecast their future developments and tendencies. In order to achieve this objective, the multivariate cluster analysis was applied with the help of the SPSS program, for data provided by the Eurostat for several innovation, sustainable development and contextual indicators. In a first step, for each of the analyzed countries, the values of the indicators have been collected for the same period and the correlations among them have been determined. In the second phase the number of clusters and the cluster membership of each country was determined, by running the Ward cluster analysis. Based on the results, the characteristics of each cluster of countries was defined.